Applying the Growth Identification and Facilitation Framework The Case of Nigeria - Lin, Justin Yifu (The World Bank, 2011)
This paper applies the Growth Identification and Facilitation Framework developed by Lin and Monga (2010) to Nigeria. It identifies as appropriate comparator countries China, India, Indonesia, and Vietnam, and selects a wide range of industries in which these comparator countries may be losing their comparative advantage and which may therefore lend themselves to targeted interventions of the government to fast-track growth. These industries include food processing, light manufacturing, suitcases, shoes, car parts, and petrochemicals. The paper also discusses binding constraints to growth in each of these value chains as well as mechanisms through which governance-related issues in the implementation of industrial policy could be addressed